Report on the 6th ADBIS’2002 conference - Bieliková, Mária; Návrat, Pavol; Manolopoulos, Yannis (Computing and Informatics, 2012)
The 6th East European Conference ADBIS 2002 was held on September~8--11, 2002 in Bratislava, Slovakia. It was organised by the Slovak University of Technology (and, in particular, its Faculty of Electrical Engineering and Information Technology) in Bratislava in co-operation with the ACM SIGMOD, the Moscow ACM SIGMOD Chapter, and Slovak Society for Computer Science. The call for papers attracted 115 submissions from 35~countries. The international program committee, consisting of 43 researchers from 21 countries, selected 25 full papers and 4 short papers for a monograph volume published by the Springer Verlag. Beside those 29 regular papers, the volume includes also 3 invited papers presented at the Conference as invited lectures. Additionally, 20 papers have been selected for the Research communications volume. The authors of accepted papers come from 22~countries of 4 continents, indicating the truly international recognition of the ADBIS conference series. The conference had 104 registered participants from 22~countries and included invited lectures, tutorials, and regular sessions. This report describes the goals of the conference and summarizes the issues discussed during the sessions.